Effects of varying levels of protein supplement on voluntary intake, nutrient utilization and water metabolism in buffalo bullocks fed wheat-straw as basal ration - PUNIA, B S; DAHIYA, S S; CHAUHAN, T R (The Indian Journal of Animal Sciences, 2013)
Murrah bullocks (12;63 months, 400kg) divided into 3 groups of 4 each were offered wheat straw ad lib. Deoiled (solvent extracted) groundnut-cake was supplemented @ 0.5, 1.5 and 2.25kg, respectively, in treatments 1,2 and 3. The total crude protein contents of the 3 dietary treatments were about 5, 9 and 12% respectively. Average dry matter intake (9.2, 10.2 10.1kg, in groups 1,2 and 3) increased with the increase of groundnut-cake in the diet. Apparent digestibilities (percent) in groups 1, 2 and 3 were estimated for DM (52.7, 56.0, 60.2), OM (53.5, 57.3, 61.5), CP (46.7, 67.5, 74.6), CF (59.5, 59.2, 61.1), EE (35.5, 56.7, 58.7), and NFE (49.4, 53.4, 58.4). DCP and TDN of the 3 rations were calculated to be 2.4 and 47.5, 6.1 and 51.3 and 9.0 and 55.6, respectively, in groups 1,2 and 3. In groups 1,2 and 3, the values (litres) for water drunk (27.6, 29.8, 30.6), feed water (0.5,05,05), metabolic water (2.6, 3.0, 3.2), and losses through faeces (16.6 19.4, 16.3) and urine (5.2, 6.8, 8.1) indicated that evaporative loss of water (8.99, 7.09, 9.92) was not significantly different among the 3 treatment groups. Consequently, Voluntary intake and nutrient utilization on a poor quality diet like wheat straw may be improved by increasing the protein content of the diet with protein supplements.